The role of MiRNA in polycystic ovary syndrome (PCOS) - Chen, Baiqi; Xu, Ping; Wang, Jing; Zhang, Chunping (Gene, 2019)
Polycystic ovary syndrome (PCOS) is a prevalent endocrine disorder in reproductive-aged women. Clinical manifestations include hyperandrogenism, chronic anovulation, polycystic ovaries and being frequently accompanied by insulin resistance (IR) and obesity. MicroRNAs (miRNAs) are short non-coding RNAs which are involved in the regulation of gene expression at the post-transcriptional level. Altered miRNAs levels have been showed to be associated with a variety of diseases including diabetes, endometriosis and cancer. In recent years, more and more evidence suggests abnormal expression of miRNAs are detected in granulosa cells, theca cells, adipose tissue, follicular fluid, serum and peripheral blood leukocytes of women with PCOS and display vital role in the occurrence and development of PCOS. This will shed light on new strategies for the diagnosis and treatment of this syndrome. In this paper, we will review the recent research on miRNAs with respect to PCOS. •MiRNAs are involved in broad physiological processes.•Dysregulated miRNAs could be detected within cells and extracelluar fluids of Polycystic Ovary Syndrome patients and were involved in the pathogenesis of Polycystic Ovary Syndrome.